Fourth Ezra and Second Baruch : reconstruction after the fall - Henze, Matthias. (Supplements to the Journal for the Study of Judaism, 2013)
The two Jewish works that are the subject of this volume, 4 Ezra and 2 Baruch , were written around the turn of the first century CE in the aftermath of the Roman destruction of the Second Temple. Both texts are apocalypses, and both occupy an important place in early Jewish literature and thought: they were composed right after the Second Temple period, as Rabbinic Judaism and early Christianity began to emerge. The twenty essays in this volume were first presented and discussed at the Sixth Enoch Seminar at the Villa Cagnola at Gazzada, near Milan, Italy, on June 26-30, 2011. Together they reflect the lively debate about 4 Ezra and 2 Baruch among the most distinguished specialists in the field. The Contributors are: Gabriele Boccaccini; Daniel Boyarin; John J. Collins; Devorah Dimant; Lutz Doering; Lorenzo DiTommaso; Steven Fraade; Lester L. Grabbe; Matthias Henze; Karina M. Hoogan; Liv Ingeborg Lied; Hindy Najman; George W.E. Nickelsburg; Eugen Pentiuc; Pierluigi Piovanelli; Benjamin Reynolds; Loren Stuckenbruck; Balázs Tamási; Alexander Toepel; Adela Yarbro Collins